1973
DOI: 10.1177/003072707300700410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct drilling and reduced cultivation on soil conditions for root growth

Abstract: The two aspects of soil conditions and root growth in reduced cultivation systems are reviewed. Generally, an uncultivated soil is characterized by increased mechanical strength, reduced porosity greater moisture, more organic matter and structural stability at the surface, more earthworms and the development of nutrient gradients. Effects on root growth are much more variable and reflect the indirect relationship that exists between bulk soil properties and root growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 27 publications
0
16
1
1
Order By: Relevance
“…Na camada inferior (10-20 cm) e entre as sucessões de culturas (em ambas as profundidades), as diferenças entre os teores de C-orgânico não foram marcantes. Em experimentos de longa duração, realizados em diferentes regiões, têm sido comprovados os efeitos do acúmulo de resíduos vegetais na superfície do solo pelo sistema de plantio direto, formando camadas com teores diferenciados de matéria orgânica e nutrientes (Triplett & Doren, 1969;Shear & Moschler, 1969;Moschler et al, 1972;Cannel & Finney, 1973;Lal, 1975;Blevins et al, 1977;Muzilli, 1983;Sidiras & Pavan, 1985;Sá, 1993). A interação entre fatores climáticos (temperatura, precipitação) e acúmulo de restos culturais na superfície do solo resulta em melhoria ambiental para a biomassa microbiana, aumentando a sua atividade.…”
Section: Resultados E Discussão Distribuição Dos Teores De Carbono Orunclassified
“…Na camada inferior (10-20 cm) e entre as sucessões de culturas (em ambas as profundidades), as diferenças entre os teores de C-orgânico não foram marcantes. Em experimentos de longa duração, realizados em diferentes regiões, têm sido comprovados os efeitos do acúmulo de resíduos vegetais na superfície do solo pelo sistema de plantio direto, formando camadas com teores diferenciados de matéria orgânica e nutrientes (Triplett & Doren, 1969;Shear & Moschler, 1969;Moschler et al, 1972;Cannel & Finney, 1973;Lal, 1975;Blevins et al, 1977;Muzilli, 1983;Sidiras & Pavan, 1985;Sá, 1993). A interação entre fatores climáticos (temperatura, precipitação) e acúmulo de restos culturais na superfície do solo resulta em melhoria ambiental para a biomassa microbiana, aumentando a sua atividade.…”
Section: Resultados E Discussão Distribuição Dos Teores De Carbono Orunclassified
“…Similar results were obtained by Dev et al (1970). Under temperate conditions, Arnott and Clement ( I 966) also found increased nitrogen mineralization in ploughed soil, but Tomlinson I 73), quoted by Cannell and Finney (1973), did not find significant d i i erences in soil nitrate content between directdrilled and ploughed treatments.…”
Section: Introductionmentioning
confidence: 96%
“…Reduced tillage frequently results in higher soil bulk densities after planting (Baeumer and Bakermans 1973;Cannell and Finney 1973;Hamblin and Tennant 1979), but the effect of bulk density on P uptake is unclear. Prummel (1975) found in field studies in The Netherlands that high bulk densities reduced root growth and increased the need for P fertilizer, whereas Ellis et al (1977) found in the U.K. that reducing tillage had no effect on P uptake, despite increased bulk density and reduced root extension.…”
Section: Introductionmentioning
confidence: 99%